Tin Oxide Quantum Dots and Poly(Ortho-Chloroaniline)-Supported SnO2 Nanocomposite for Dye-Wastewater Photocatalysis, Reuse, and Seed-Germination Assessment - Walied A. A. Mohamed; Hala T. Handal; Mahmoud A. M. Ahmed; Nahla M. Badawy; Mona M. Fawzy; Ibrahem A. Ibrahem; Hanan A. Mousa; Hoda R. Galal; M. S. A. Abdel-Mottaleb; Ammar A. Labib (Water, Air, & Soil Pollution, 2026)

In-silico Exploration of Marine Algae-derived Compounds as the Potential Inhibitors of Polycomb Group Ring Finger 4 Protein - Md Al Saber; Sowmitro Das; S. M. Istiaque Hamim; Sadia Jannat Tauhida; Kazi Sneha Chhando; Partha Biswas; Mohaimenul Islam Tareq; Faria Khondokar Noumi; Shaharia Akter Borsha; Labib Sahariar Siam; Roney Miah; Md. Nazmul Hasan (Journal of Pharmaceutical Innovation, 2026)

Exploring the effect of bronopol exposure length on the suppression of Aeromonas hydrophila infection in nile tilapia (Oreochromis niloticus L.) - Zizy I. Elbialy; Eman M. Moustafa; Amira A. Omar; Abdallah S. Salah; Ahmed Elsheshtawy; Mohammed M. Zayed; Marwa F. Abdel-Kader; Hani Y. Labib; Hossam I. Kadira; Dina B. Barsem; Ahmed E. Elshafey; Sayed M. Aboleila; et al. (Veterinary Research Communications, 2026)

Male reproductive toxicity induced by chronic dinotefuran exposure: In vivo and in silico evidence and the ameliorative role of Rosmarinus officinalis - Samah S. Arafa; Ibrahim.M. Ammar; Ragaa A. Eisa; Mariam E. Labib; Ahmed M. Atwa; Marwa O. Gabr (Reproductive Toxicology, 2026)

Quantitative Health Impact Assessment of Environmental Exposures Linked to Urban Transport and Land Use in Europe: State of Research and Research Agenda - James Woodcock; Lambed Tatah; Paulo Anciaes; Zorana Andersen; Ronita Bardhan; Xuan Chen; Audrey de Nazelle; Ulrike Gehring; Stefan Gössling; Marco Helbich; Gerard Hoek; SM Labib; et al. (Current Environmental Health Reports, 2025)
In this article, we summarise recent developments, identify gaps, and propose a research agenda for quantitative health impact assessment (HIA) of environmental exposures linked to urban transport and land use. This is based on a workshop of 30 experts, complemented by targeted literature identified by participants to illustrate the state of research and practice gaps. The practice of quantitative HIA in urban transport and land use interventions covers a diverse range of methods, models, and frameworks. The selection of an appropriate model depends upon the use case, i.e., the research question, resources and expertise, and application. The plurality of models can be a strength if differences are explicit and their implications are understood. A major gap in most assessments and frameworks is the lack of equity consideration. This should be integrated into all stages of the HIA, considering exposures, susceptibility, disease burden, capacity to benefit, household budgets, responsibility for harm, and participation in the process. Scenarios of environmental exposures in urban transport and land use interventions are often overly simple, while the scenario design process of spatial planning is often opaque. Researchers should specify the involvement of stakeholders and the data, evidence, or behavioural model used to construct the scenario. Recent developments in exposure assessment (remote sensing and modelling) have increased the capacity to conduct HIAs for small geographies at scale. At the same time, advances in simulation have enabled the representation of behaviours at high spatial and temporal resolution. The combination can enable person-centric measures accounting for location, activities, and behaviours, with HIA proceeding ahead of epidemiology. Most HIAs still use Comparative Risk Assessment. This is suitable for estimating the disease burdens of environmental exposures, but more advanced longitudinal methods are better suited for studying interventions. Beyond health outcomes, well-being must be incorporated. The monetisation of health outcomes through welfare economics remains contentious. Representation of uncertainty is increasingly acknowledged. Value of Information methods can inform where new data collection would most efficiently reduce final result uncertainty. In the context of the climate crisis and related environmental limits, methods are needed that consider adaptation alongside mitigation and prevention and test robustness to an increasingly unstable future.

Zolmitriptan niosomal transdermal patches: combating migraine via epigenetic and endocannabinoid pathways and reversal of migraine hypercoagulability - Nancy Abdel Hamid Abou Youssef; Gihan Salah Labib; Abeer Ahmed Kassem; Nesrine S. El-Mezayen (Drug Delivery and Translational Research, 2025)
Conventional zolmitriptan (ZOL) has limited oral bioavailability, many adverse effects, and poor membrane penetrability that negatively influences its accessibility to its 5-HT 1B/1D receptor binding pocket, located transmemberanous. This work aimed at preparing transdermal ZOL-nanoformulation (niosomes) to surpass these limitations and to explore novel antimigraine mechanisms for ZOL via modulation of the epigenetically-altered chronification genes (RAMP-1, NPTX-2) or microRNAs and affecting the endocannabinoid CB-1/MAPK pathway. The prepared ZOL niosomes (F sp60/6−1:1 ) exhibited %EE of 57.28%, PS of 472.3 nm, PDI of 0.366, and ZP of -26 mV were cast into patch with content uniformity of 93.12%, maintained endurance after 200-times folding, no interaction between its components (FT-IR), a biphasic release pattern and good stability after storage at 4 °C for 6 months. In-vivo ZOL-patch application in rats with nitroglycerin-induced migraine showed significant management of migraine pain symptoms and photophobia assessed behaviorally, decreased brain levels of the trigeminal neuronal activation marker (c-fos), the migraine pain neurotransmitter (CGRP) and the serum levels of different migraine pain markers (substance P, nitric-oxide, and TNF-α). It also significantly decreased RAMP-1, NPTX-2, miR-382-5p, and CB-1/MAPK gene expression reflecting improved efficacy and brain receptors delivery to a much greater extent than conventional ZOL has done. Additionally, this nanoformulation significantly opposed migraine-induced platelet activation and hypercoagulable status in both central and peripheral circulations as evidenced by the significant decrease in adenosine diphosphate, thrombin, factor X, CD41, and Von-Willebrand factor levels assessed peripherally and centrally. TPF sp60/6−1:1 significantly improved ZOL efficacy and accessibility to brain-receptors to a much greater extent than conventional ZOL-solution. KeywordsEndocannabinoid receptors; Epigenetically-altered genes; Hemostatic pathways; Niosomal patch; Transdermal; Zolmitriptan Graphical abstract

Approaches of Inducing Tolerance to Murine Schistosomiasis mansoni applying Biomphalaria and Bulinus Proteins - Hanan S. Mossalem; Sami Mohamed Nasr; Azza Moustafa Fahmy; Shimaa Atta; Gehan Labib Abuelenain (Acta Parasitologica, 2025)
Background The freshwater snails Biomphalaria alexandrina and Bulinus trancatus are key contributors to the transmission of S. mansoni and S. haematobium , respectively, for being their intermediate hosts. Objectives This research study aimed to investigate the potency of the nucleoproteins (NPs) extracted from both snail species on the host immune reactions as an approach to developing a potential vaccine. Methods Three groups of six-week-old Swiss-Webster mice ( n = 18; 15–20 g each) were injected intraperitoneally for three consecutive weeks with single doses (once a week) of B. alexandrina , B. truncatus , or a mixture of their nucleoproteins (50 µg each). On day 21st, the nucleoprotein-treated mice altogether, with six more mice, received subcutaneously S. mansoni cercariae (60/mouse). Eight weeks later, the experimental mice were sacrificed for evaluation of certain parasitological, molecular and immunological responses. Results The data of mice immunized with the various types of nucleoproteins showed a significant increase of FAS/R gene expressions in hepatic tissues and anti-IgG antibody levels in sera on the one hand and a significant decrease of worm loads and β-actin/R gene expression levels on the other hand when compared to the infected control mice. Conclusion These findings highlight the role of snails in immunomodulation and shed light on the possibility of antagonizing effects that might occur when the nucleoproteins of different species are mixed. Moreover, this research study might promote the literature spotting the importance of snail proteins against schistosomiasis.

Assessment of zootechnical parameters, intestinal digestive enzymes, haemato-immune responses, and hepatic antioxidant status of Pangasianodon hypophthalmus fingerlings reared under different stocking densities - Mohamed A. A. Zaki; Hala Saber Khalil; Belal W. Allam; Riad H. Khalil; Mohammed F. El Basuini; Abd El-Aziz M. Nour; Eman M. H. Labib; Islam S. E. Elkholy; Marc Verdegem; Hany M. R. Abdel-Latif (Aquaculture International, 2023)
A 3-month experiment was designed to investigate the effects of different stocking densities on growth, stress markers, intestinal digestive enzymes, hepatic antioxidant biomarkers, serum immunity, and survivability of striped catfish, Pangasianodon hypophthalmus . The relationship between fish stocking densities and water quality parameters was also assessed. Healthy fish ( n = 1260 individuals, 17.52 ± 0.20 g) were raised in twelve fiberglass tanks. Triplicate fish groups with stocking densities of 60, 90, 120, or 150 fish per 1 m 3 were designed, further referred to as SD60, SD90, SD120, and SD150 groups. Fish feeding was done using a commercially purchased well-balanced diet three times per day with a feeding rate of 3% of the wet fish weight. Results revealed that un-ionized ammonia, nitrite, and pH were significantly elevated, and dissolved oxygen levels were decreased significantly with increasing the stocking densities. The survival rates and growth significantly decreased with increasing fish stocking densities. The intestinal lipase, protease, trypsin, and amylase enzymes decreased significantly ( P 3 . Conversely, serum stress biomarkers (such as blood glucose and cortisol), transaminases, alkaline phosphatase, and blood urea nitrogen were significantly elevated with increasing stocking densities. Hepatic CAT, SOD, and T-AOC were decreased; meanwhile, hepatic MDA levels were significantly increased, together with the stocking rates. In the end, we found that the SD150 group recorded the lowest growth rates, immune responses, and antioxidant capacity and the highest stress markers as blood glucose and cortisol. In this context, we can conclude that the stocking 60 fish/m 3 resulted in better growth, survival, immunity, antioxidant status, and overall performances of striped catfish. Graphical Abstract

Controlled Drainage and Irrigation Regime for Improving Some Soil Properties and Wheat Production, Sahl El-Tina, Sinai Peninsula, Egypt - A. S. El-Hassanin; M. R. Samak; Y. Atta; Somma M. H. Labib (Water Conservation Science and Engineering, 2022)

Eco-Friendly Tadalafil Surfactant-Free Dry Emulsion Tablets (SFDETs) Stabilized by In Situ Self-Assembled Aggregates of Natural Oil and Native Cyclodextrins - Shaimaa M. Badr-Eldin; Gihan S. Labib; Mona H. Aburahma (AAPS PharmSciTech, 2019)

Comparative transcriptomic analyses to scrutinize the assumption that genotoxic PAHs exert effects via a common mode of action - S. Labib; A. Williams; C. H. Guo; K. Leingartner; V. M. Arlt; H. H. Schmeiser; C. L. Yauk; P. A. White; S. Halappanavar (Archives of Toxicology, 2016)

Discrepancies in Bacterial Recovery from Dental Unit Water Samples on R2A Medium and a Commercial Sampling Device - Richard S. Smith; Silvia A. Pineiro; Ruby Singh; Elaine Romberg; Mohamed E. Labib; Henry N. Williams (Current Microbiology, 2004)